(untitled) (Revista Contexto & Saúde, 2026)
Objective: to analyze pregnant women’s knowledge and attitudes regarding the prevention and transmission of syphilis. Methods: an analytical cross-sectional study carried out in two public maternity hospitals in Teresina, Piauí, between November 2023 and January 2024, involving 165 pregnant women. Data were collected through the application of a validated questionnaire covering sociodemographic aspects, sexual behavior, knowledge, and attitudes toward syphilis prevention and transmission. Data were analyzed using Spearman’s correlation, Pearson’s chi-square test, and binomial logistic regression. The magnitude of association between categorical variables was assessed using the odds ratio. Results: among the 165 pregnant women, 71.5% were aged 30 years or younger, 69.1% were married or living with a partner, and 70.1% had more than nine years of schooling. Regarding sexual behavior, 58.2% had their first sexual intercourse between ages 15 and 19, 43% reported not using a condom during their first sexual intercourse, and 19.4% had had more than 10 sexual partners over their lifetime. Regarding the prevention and transmission of syphilis, 45.5% had regular knowledge and 37% had inadequate knowledge. Negative attitudes toward prevention and transmission of the disease predominated (40%). Regular and adequate knowledge showed statistical significance with very positive and positive attitudes of pregnant women toward syphilis prevention and transmission (p<0.05). Conclusion: there was a correlation between pregnant women’s knowledge and attitudes regarding syphilis, highlighting that those with greater knowledge had better attitudes toward preventing and understanding the transmission of the disease.